Komunikasi Pemasaran Hotel seiring bertumbuhnya Homestay Daring: Kasus Hotel Berbintang di Jawa - Edvi Gracia Ardani; Anwar Basalamah (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2020)
In the information age of the 21st century today, various peer-to-peer platforms have emerged, collectively known as platform-based economies, which are now used by many groups around the world, especially for the accommodation industry in the form of homestay-based in network or online. For the public, this platform provides easy accommodation for trips to areas of interest to explore, especially for rural tourism. As a provider of accommodation services, of course the competition with commercial hotels is very strong. The phenomenon that exists in various countries in the world shows, this platform is a threat to hotel managers who certainly provide rooms at prices higher than online-based homestays. The impact is certainly not only on the sales strategy, but also on the communication strategy. The platform threat becomes disruptive where this threat can change the management pattern of the accommodation business due to different rules and can make hotel managers think hard to change their hotel communication strategy or not at all. The availability of a free platform in the hotel chain provides hope for hotel managers to explore possibilities and anticipate perceived disruption.